Strategy and Impact Analysis of Change Management on ERP System Implementation (Case Study in PT.XYZ) - Pamungkas, Ragil Asih; Imaroh, Tukhas Shilul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to evaluate the strategy and impact of change management in implementing the Enterprise Resource Planning (ERP) system in the Accounting and Finance division of PT. XYZ. The approach used is qualitative with a case study method, where data is collected through in-depth interviews and direct observation of ERP implementation. Research participants consisted of employees at various levels who provided insight into their challenges and experiences in adapting to the new system.The research results reveal that resistance to change, high workload, and differences in competence and understanding among employees are the main obstacles that hinder the success of ERP implementation. This research also shows that effective communication and ongoing training are instrumental in overcoming these obstacles. In addition, more structured workload management and the preparation of clear standard operating procedures (SOP) can increase implementation efficiency.Based on these findings, this research suggests that PT. XYZ strengthens change management through better communication, more intensive training, and more optimal human resource management during the transition. The implications of this research emphasize the importance of organizational preparation in facing major changes and the important role of managerial support in the success of implementing an ERP system effectively.